Cruise ship suppliers: A field study of the supplier relationship characteristics in a service supply chain. (October 2015) - Véronneau, Simon; Roy, Jacques; Beaulieu, Martin
Abstract: Given the significance of the service industry, the role of global service supply chains is becoming an important new area of research. This paper examines the ways suppliers positively contribute to service quality in the cruise industry and defines the nature of the relationships between a major cruise line corporation and its suppliers. The data stems from a 4-year field study of a large cruise line corporation and twenty-one semi-structured interviews conducted on board and shore-side with senior management. Additionally logistics processes were observed and analyzed through an ethnographic lens. The characteristics of the relationship are described and hence enabling a better understanding of the service quality creation among suppliers. The results have implications for service and hospitality supply chains in such settings as large resorts and humanitarian logistics. Highlights: An important aspect of being a cruise supplier is flexibility, and the ability to meet an ad hoc demand. The best suppliers will foster cooperative efforts in developing proper SOPs for the use of their supplies. In order to keep suppliers synced with the organization's culture it is essential to have socialization mechanisms. One of the most effective socialization mechanisms is the suppliers' experiencing the product.